Training and Development Practices and Employees’ Performance in Selected Manufacturing Companies in Nigeria - Taiwo, Sunday F.; Dr. Alase, Peter O.; Dr. Hassan, Tolani, A.; Okusanya, Adedoyin, O. (International Journal of Engineering and Management Research, 2021)
Managing workforce diversity in manufacturing organisations has been a problem all over the world including Nigeria. Manufacturing organisations in Nigeria continue to experience occasional drop in performance due to employees’ apathy and non-challant attitudes as a result of high level of dissatisfaction caused by inadequate attention to training and development practices. This study assessed the relationships between training and development practices and employees’ performance in selected manufacturing companies in Nigeria. A cross sectional survey research design was employed, and out of the 1,568 copies of questionnaire that were administered proportionally in the selected manufacturing companies, 1,153 copies were retrieved and found useful. Data were analysed using descriptive statistics and the hypotheses were tested using Analysis of Variance (ANOVA). The results of the findings show f-statistics of 223.717 and so, there is a significant relationship between training and development practices and employees’ performance among Nigerians working in the selected manufacturing companies. Also, f-statistics of 244.391 shows a significant relationship between training and development practices and employees’ performance among other nationals in the selected MNCs. The study concluded that there are significant relationships between training and development practices and employees’ performance in selected manufacturing MNCs in Nigeria.